Expression of prostaglandin receptors inChlamydia trachomatis‐infected recurrent spontaneous aborters. Issue 6 (June 2016) - Singh, Namita; Prasad, Priya; Singh, Laishram Chandreshwar; Das, Banashree; Rastogi, Sangita
Abstract : N/A: A study was undertaken to quantify the expression of prostaglandin (PG) receptors and find the effect of gestational age on expression of PG receptor genes in Chlamydia trachomatis ‐infected recurrent spontaneous aborters (RSA). Endometrial curettage tissue (ECT) was collected from 130 RSA (Group I) and 100 age‐matched controls (Group II) at the Department of Obstetrics and Gynecology, Safdarjung Hospital, New Delhi (India). PCR was performed for diagnosis of C. trachomatis cryptic plasmid; mRNA expression of PG receptor genes was assessed by real‐time PCR (q‐PCR), while serum progesterone/estrogen levels were determined by respective commercial kits. Data were evaluated statistically. A total of 15.4 % RSA (GroupI) were diagnosed as C. trachomatis ‐positive (200 bp), whereas controls were uninfected. q‐PCR showed significant upregulation ( P <0.0001) of PGE2 (EP‐1, EP‐2, EP‐3, EP‐4), PGF2α (FP) and PGI2 (IP) receptors in Group I versus Group II. The expression of PG receptors increased significantly with advanced gestational age ( P <0.002); however, only contractile receptors, EP‐1, EP‐3 and FP, were positively correlated with gestational age in Group‐I. In infected RSA, mean serum progesterone level was significantly low ( P <0.0001) while serum oestrogen was high ( P <0.0001). Overall, the data suggest that increased expression of PG receptors, particularly contractile gene receptors (EP‐1, EP‐3, FP), with advanced gestational age and altered steroid levels could be a possible risk factor for abortion in Chlamydia ‐infected RSA.